The study of carbon nanomaterials by IR-Fourier spectroscopy, obtained by the action of an ultrasonic field on graphite - Б.А. Байтимбетова; К.С. Толубаев; Ю.А. Рябикин; Д.О. Мурзалинов; Б.А. Жаутиков; Г.С. Даирбекова (Қарағанды университетінің хабаршысы. Физика сериясы)
In this work, the absorption lines corresponding to nanomaterials (nanotubes, nanofibers, graphene), as well as vibrational spectra in the studied samples of graphene structures obtained by processing an ultrasonic field on an aromatic hydrocarbon and pure graphite, are studied by IR-Fourier spectroscopy. With an increase in time in the studied spectra of ultrasonic treatment on pure graphite, absorption bands are observed in the frequency range of ν= 2967,7 cm-1, 2926,1 cm-1, 2853 cm-1, 1449 cm-1, related to stretching and deformation vibrations of the bond C-H of saturated aromatic hydrocarbons. The spectra of carbonyl (carbon) compounds of the C-C bond are also noted in the regions of the absorption bands: 1449,9 cm-1÷1652,6 cm-1. This means that in the IR spectra, with an increase in the time of sonication, the carbon formations of asymmetric stretching vibrations of C-C bonds increase. In these frequency ranges, the absorption bands corresponding to adsorbed benzene are not observed. With an increase in the processing time of the samples, the absorption band of OH hydroxyl groups is not observed. In the samples under study, numerous aromatic carbon-carbon bonds are observed, due to the collective groups of vibrations of carbon nanomaterials (graphene structures, nanofibers, single-layer and multilayer carbon nanotubes, etc.).